Entrepreneurship, Institutions and Economic Dynamism: Lessons from a Comparison of the United States and Sweden - Pontus Braunerhjelm; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2012)
The purpose of this research endeavorin the form of eight articlesto be published in 2013 in a Special Section of Industrial and Corporate Change is to further our understanding of the extent, character and orientation of entrepreneurial activity in todays wealthy countries. This is done by means of detailed studies of particular aspects of the rules of the game deemed to be of particular importance for entrepreneurship, innovation-based firm growth and its ensuing impact on the economy. Particular aspects of entrepreneurship and economic dynamism are covered by pairs (or in one case three) coauthors, who are renowned specialists in the area and with deep knowledge of the pertinent institutions in Sweden and the US. These two countries have been argued to be located at either end of the spectrum of the types of capitalism with respect to the degree coordination and government intervention. This introductory essay sets off by giving a short overview of the institutional differences that distinguish these economies, but also stresses that convergence has occurred in the last decades in several respects. Still, as is obvious from the summary of the eight comparative analyses included in the Special Section, considerable differences remain. These constitute the basis for the concluding policy discussion.
Keywords: G28; H30; K30; L26; L53; O43; O57; 330; Entrepreneurship; Innovation; Institutions; Firm growth; Economic dynamism